Das Selbst im Blick: Interdisziplinäre Perspektiven zur Selfie-Forschung - Steimer, A. Kristina, M.A.; Paganini, Claudia; Filipović, Alexander, M.A. (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Every question about the selfie, every research method and every research finding offers insights into the complexity of this mass media phenomenon. In the process, questions are raised about the structural conditions under which communication and expression take place, while the constellations between the body and the environment, between the self and technology are put up for discussion anew. This interdisciplinary anthology traces dominant references to this research subject, addressing four thematic areas in detail: Corpus formation: How is the selfie accomplished? Identity: Who does the selfie constitute? The history of ideas: Where does the selfie come from? Participation: What does the selfie change?With contributions bySimone Birkel | Karin Boczek | Johannes Brunner | Noreen van Elk | Alexander Filipović | Celine Frohnapfel | Winfried Gerling | Sophie Hepach | Maya Hermens | Henriette Hufgard | Johannes Kirschenmann | Korbinian Klinghardt | Krisha Kops | Lydia Isabella Korte | Julian Kraemer | Katharina Lobinger | Oana Lünenborg | Zoe Mayer | Claudia Paganini | Olivia Rademacher | Jonas Schützeneder | A. Kristina Steimer | Wolfgang Ullrich | Silvana Weber | Tobias Wittchen